Family functioning and levels of learning achievement of basic education students - Estrada-Araoz, Edwin G. (2020)
The research objective was to establish the relationship that exists between family functioning and the levels of learning achievement of the students of the Alipio Ponce Vásquez Educational Institution in Puerto Maldonado. The research approach was quantitative, the design was non-experimental and the descriptive type was cross-sectional correlational. The population was made up of all the fifth and sixth grade students of the primary level of the Alipio Ponce Vásquez Educational Institution and a sample of 96 students was used, which was obtained by means of a probability sampling. The technique used for data collection was the survey, in the case of the variable family functioning and the documentary analysis in the case of the variable levels of learning achievement. On the other hand, the data collection instruments were the Family Cohesion and Adaptability Assessment Scale and the consolidated comprehensive assessment report at the primary level. The results indicated that there is a moderate, direct and significant correlation between family functioning and student learning achievement levels. Spearman's rho correlation coefficient was 0.501 with a p-value below the level of significance (p = 0.000 <0.05). It was concluded that the family functioning perceived by the students is unhealthy and tends to be dysfunctional, which results in the students not reaching optimum levels of learning achievement.